Planning and Economic Coordination Challenges after the 18th Constitutional Amendment - Tahir, Pervez; Tahir, Nadia (Journal of Development Policy Research and Practice (JoDPRP), 2023)
The 18th Amendment has significantly changed the Constitution of Pakistan. It has increased the number of subjects in the provincial sphere. This expanded autonomy was fiscally supported by the 7th National Finance Commission (NFC) Award, which reversed the federal-provincial resource distribution formula in favour of the provinces. In this paper, the authors find that the new structure of planning and economic coordination required to implement these fundamental changes is not in place. The Planning Commission (PC), i.e., Ministry of Planning Development & Special Initiatives, continues to be a think tank of the federal government rather than the federation. Its visioning for the long-term and planning documents for the medium-term on an annual basis are found to be against the spirit of the amended Constitution, which stipulates a participatory process. The authors’ analysis leads to the conclusion that the Commission should be an independent secretariat of the Council of Common Interests (CCI) to ensure effective coordination. Towards this end, members of the Commission should also represent the provinces. Devolution to the local level, however, will continue to be a challenge.